The Andean Community in the global context Post-reengineering 2014: a look from the collective action - Reggiardo, Giulliana (2021)
The Andean Community (CAN) is a regional integration bloc and its progress has always been in debate. The present essay makes use of the theoretical tool of the political sciences, specifically, the theory of collective action, for the analysis of the integration process from the 2014 reengineering onwards. The results of the analysis allow to determine that each member gives a different valuation to the identification of the so-called collective assets of the block. Under this logic, this assessment has a direct impact on the success of the international organization in the context of a globalization that, increasingly, requires global results from a governance perspective.